DEFINITION lt_blt()
TYPE =
∀x:nat.∀y:nat.(lt y x)→(eq bool (blt y x) true)
BODY =
assume x: nat
we proceed by induction on x to prove ∀y:nat.(lt y x)→(eq bool (blt y x) true)
case O : ⇒
the thesis becomes ∀y:nat.(lt y O)→(eq bool (blt y O) true)
assume y: nat
suppose H: lt y O
(H0)
by cases on H we prove (eq nat O O)→(eq bool (blt y O) true)
case le_n ⇒
the thesis becomes (eq nat (S y) O)→(eq bool (blt y O) true)
suppose H0: eq nat (S y) O
(H1)
we proceed by induction on H0 to prove <λ:nat.Prop> CASE O OF O⇒False | S ⇒True
case refl_equal : ⇒
the thesis becomes <λ:nat.Prop> CASE S y OF O⇒False | S ⇒True
consider I
we proved True
<λ:nat.Prop> CASE S y OF O⇒False | S ⇒True
<λ:nat.Prop> CASE O OF O⇒False | S ⇒True
end of H1
consider H1
we proved <λ:nat.Prop> CASE O OF O⇒False | S ⇒True
that is equivalent to False
we proceed by induction on the previous result to prove eq bool (blt y O) true
we proved eq bool (blt y O) true
(eq nat (S y) O)→(eq bool (blt y O) true)
case le_S m:nat H0:le (S y) m ⇒
the thesis becomes ∀H1:(eq nat (S m) O).(eq bool (blt y O) true)
suppose H1: eq nat (S m) O
(H2)
we proceed by induction on H1 to prove <λ:nat.Prop> CASE O OF O⇒False | S ⇒True
case refl_equal : ⇒
the thesis becomes <λ:nat.Prop> CASE S m OF O⇒False | S ⇒True
consider I
we proved True
<λ:nat.Prop> CASE S m OF O⇒False | S ⇒True
<λ:nat.Prop> CASE O OF O⇒False | S ⇒True
end of H2
consider H2
we proved <λ:nat.Prop> CASE O OF O⇒False | S ⇒True
that is equivalent to False
we proceed by induction on the previous result to prove (le (S y) m)→(eq bool (blt y O) true)
we proved (le (S y) m)→(eq bool (blt y O) true)
by (previous H0)
we proved eq bool (blt y O) true
∀H1:(eq nat (S m) O).(eq bool (blt y O) true)
(eq nat O O)→(eq bool (blt y O) true)
end of H0
by (refl_equal . .)
we proved eq nat O O
by (H0 previous)
we proved eq bool (blt y O) true
∀y:nat.(lt y O)→(eq bool (blt y O) true)
case S : n:nat ⇒
the thesis becomes ∀y:nat.(lt y (S n))→(eq bool (blt y (S n)) true)
(H) by induction hypothesis we know ∀y:nat.(lt y n)→(eq bool (blt y n) true)
assume y: nat
we proceed by induction on y to prove (lt y (S n))→(eq bool (blt y (S n)) true)
case O : ⇒
the thesis becomes (lt O (S n))→(eq bool (blt O (S n)) true)
suppose : lt O (S n)
by (refl_equal . .)
we proved eq bool true true
that is equivalent to eq bool (blt O (S n)) true
(lt O (S n))→(eq bool (blt O (S n)) true)
case S : n0:nat ⇒
the thesis becomes ∀H1:(lt (S n0) (S n)).(eq bool (blt n0 n) true)
() by induction hypothesis we know
lt n0 (S n)
→eq bool <λn1:nat.bool> CASE n0 OF O⇒true | S m⇒blt m n true
suppose H1: lt (S n0) (S n)
consider H1
we proved lt (S n0) (S n)
that is equivalent to le (S (S n0)) (S n)
by (le_S_n . . previous)
we proved le (S n0) n
that is equivalent to lt n0 n
by (H . previous)
we proved eq bool (blt n0 n) true
that is equivalent to eq bool (blt (S n0) (S n)) true
∀H1:(lt (S n0) (S n)).(eq bool (blt n0 n) true)
we proved (lt y (S n))→(eq bool (blt y (S n)) true)
∀y:nat.(lt y (S n))→(eq bool (blt y (S n)) true)
we proved ∀y:nat.(lt y x)→(eq bool (blt y x) true)
we proved ∀x:nat.∀y:nat.(lt y x)→(eq bool (blt y x) true)